Elemental mercury removal over a novel starch-modified MnOx/bentonite composite - Zhou,Z; Liu,X; Xu,J; Cao,XE; Zhu,X (Fuel Processing Technology, 2019)
To improve the activity of elemental mercury (Hg0) removal over the bentonite supported MnOx material (MnOx/bentonite), a novel starch-modified MnOx/bentonite composite (MnOx/starch-bentonite) was synthesized for Hg0 capture. The Hg0 removal activity tested under the atmosphere of pure N2 and in the presence of O2 showed that the MnOx/starch-bentonite exhibited better activity and stability than MnOx/bentonite. It was evident that the Hg0 removal efficiency over the novel catalytic sorbent (BS10M2) only declined by 16.9%, while that over MnOx/bentonite fell by 68.7% after a 5 h test under the atmosphere of N2 + 6%O2 at 120 °C. The starch modification decreased the surface area but enhanced the surface activity of bentonite, and more activate sites were generated on the surface of bentonite after being impregnated with potassium permanganate (KMnO4) solution. The improved Hg0 removal performance was probably due to the generation of more Mn4+ and the newly introduced ester groups formed by the partial oxidation reaction between starch and KMnO4 on the support, which played essential roles in mercury catalytic oxidation and adsorption. The MnOx were generated in two ways: KMnO4 decomposition in a neutral solution condition and KMnO4 reduction by the starch with hydroxyl groups.